Varietal effects on methane intensity of paddy fields under different irrigation management - Asch, F.; Johnson, K.; Vo, T. B. T.; Sander, B.O.; Duong, V.N.; Wassmann, R. (Wiley, 2023)
Alternate wetting and drying irrigation (AWD) has been shown to decrease water use and trace gas emissions from paddy fields. Whereas genotypic water use shows little variation, it has been shown that rice varieties differ in the magnitude of their methane emissions. Management and variety‐related emission factors have been proposed for modelling the impact of paddy production on climate change; however, the magnitude of a potential reduction in greenhouse gas emissions by changing varieties has not yet been fully assessed. AWD has been shown to affect genotypic yields and high‐yielding varieties suffer the greatest loss when grown under AWD. The highest yielding varieties may not have the highest methane emissions; thus, a potential yield loss could be compensated by a larger reduction in methane emissions. However, AWD can only be implemented under full control of irrigation water, leaving the rainy seasons with little scope to reduce methane emissions from paddy fields. Employing low‐emitting varieties during the rainy season may be an option to reduce methane emissions but may compromise farmers’ income if such varieties perform less well than the current standard. Methane emissions and rice yields were determined in field trials over two consecutive winter/spring seasons with continuously flooded and AWD irrigation treatments for 20 lowland rice varieties in the Mekong Delta of Vietnam. Based on the results, this paper investigates the magnitude of methane savings through varietal choice for both AWD and continuous flooding in relation to genotypic yields and explores potential options for compensating farmers’ mitigation efforts.